Tabung Haji Perdana, Kuala Lumpur / Erfa Rauhah Shahril Anuar ... [et al.] - Erfa Rauhah, Shahril Anuar; Amyrul Hanif, Misrun; Muhammad Nazri, Idris; Nursyahadatul Aisyah, Abd Karim; Nur Fariha, Azhar (2019)
This report contain nine chapter in which to explain regarding our building. The content is broadly explained and it is constructed from the site visit to the case study, Tabung Haji Perdana, Kuala Lumpur. In the opening chapter 1 give detail to the company background including the information of the organization describe in detail the background of the property/case study.in this chapter we put all the building information such as the site location of building and how to access to the building. The second chapter explain on the organization maintenance management. This chapter shows the person that responsible in manage the building maintenance in the building. The third chapter explain maintenance policy that use in Tabung Haji Perdana and the mission, vision and objective in the maintenance organization. In chapter four, this chapter explain on the building technology and design. This chapter show the services that provide in the building and facilities that given to the building occupants. Furthermore, chapter five give detail regarding the building condition assessment that consist the defect sheet and the rectification cost for every defect. Chapter six explain regarding on the maintenance strategy that been used in maintenance management. Legal aspect are explained in the chapter seven. This chapter will list detail on the services and tenants agreement. Besides, we have measure the building compliance to the law. For chapter 8 detailed on the financial/maintenance budget and the forecasting for three years. Lastly, chapter nine about winding up and suggestion for the building. We have list out the problem and come out with recommendation for the building. In this chapter we also conclude overall chapters in this report.